The Role and Importance of the National University of Uzbekistan Named After Mirzo Ulugbek Which Faculty of the History in the Creation of New Educational Literature in History and Its Application to the Educational Process - Ergashev Khusan (International Journal on Integrated Education, 2023)
This article is devoted to the publication and implementation of new educational literature and textbooks created in the history of independence, as well as the importance of the National University of Uzbekistan which faculty of History in filling the existing gap.